ECOLOGY OF SOME MARINE LAGOONS ALONG THE EAST-COAST OF INDIA WITH SPECIAL REFERENCE TO THE MANAGEMENT AND UTILISATION OF THEIR RESOURCES - Menon, A. G.K.; Raman, K. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
The marine lagoons along the east coast of India such as the Chilka-lake in Orissa State, the Pulicat and the Ennore lakes near Madras, Silvatturai lagoon in Tuticorin, and the Mandapam lagoon in Ramanathapuram are shallow, vast sheets of saline water whose physical and chemical characteristics are quite different from the backwaters of the west coast and constitute distinct categories of biological environment. The main characteristic feature of these lagoons is that they are connected to the sea by a narrow mouth which is closed by a sand bar for varying periods of the year. One or more seasonal rivers open into some of these lagoons and flood them during the monsoon. The land run-off during monsoon is the only source of freshwater for others. The bar-mouth connection with the sea is opened by the thrust of the flood waters aided in some cases by human effort. This opening operates for a few months between November ? December and June - July or throughout during some years following heavy monsoon. The closure occurs by general silting and formation of a sand bar.